PROSPECTS FOR THE USE OF ALTERNATIVE FUELS - Jo‘rayev Voxidjon Islomjon o‘g‘li; Nematjonov Baxromjon Zokirjon oʻgʻli (Лучшие интеллектуальные исследования, 2023)
Abstract: This article describes the types of motor fuels for vehicles, their physical and chemical properties. The advantages of using alternative fuels as motor fuels are highlighted and the environmental and economic efficiency indicators of natural gas fuels are analyzed. Aspects of the use of different types of alternative fuels that will ensure economic stability and reduce the harmful effects on the environment are considered. More than a dozen alternative fuels are in production or under development for use in alternative fuel vehicles and advanced technology vehicles. Government and private-sector vehicle fleets are the primary users for most of these fuels and vehicles, but individual consumers are increasingly interested in them. Using alternative fuels and advanced vehicles instead of conventional fuels and vehicles helps conserve fuel and lower vehicle emissions. The world is preparing to shift to a new version of the future that releases us from a reliance on fossil fuels for transportation. Most passenger cars will switch to using batteries and electric motors.